Non-routine mathematical problems among in-service and pre-service mathematics teachers - Abdullah, A. H. (2015)
In an effort to inculcate higher order thinking skills (HOTS) among students, the form of mathematical problems given to them should be changed from routine to nonroutine problems. To achieve this, teachers need to equip themselves with the knowledge and skills related to non-routine problems. This study aimed to investigate the level of knowledge of in-service and pre-service mathematics teachers at secondary schools in which their abilities to solve and pose non-routine problems were examined. This study involved two groups of teachers: 91 in-service mathematics teachers from Johor and 50 final year students in Mathematics Education (i.e., pre-service mathematics teachers). The instruments used consisted of (1) a survey on the knowledge of mathematics teachers on non-routine problems and (2) a test containing non-routine problems to be solved and also routine problems to be changed into non-routine problems. A MANOVA test was performed to test the hypotheses stipulated. The findings showed a significant difference in posing non-routine problems among different teacher groups. The study also found that both teacher groups obtained low mean scores in solving and posing non-routine mathematical problems. In conclusion, the knowledge and skills on non-routine problems among in-service and pre-service mathematics teachers must be in alignment so that the objective of national curriculum to produce students with HOTS can be achieved.